Hypertensive patients' use of blood pressure monitors stationed in pharmacies and other locations: a cross-sectional mail survey - Mitchell C Madeline; Cohen Lauren W; Viera Anthony J; Sloane Philip D (BMC, 2008)
Abstract Background Blood pressure (BP) monitors are commonly stationed in public places such as pharmacies, but it is uncertain how many people with hypertension currently use them. We sought to estimate the proportion of hypertensive patients who use these types of monitors and examine whether use varies by demographic or health characteristics. Methods We conducted a cross-sectional mail survey of hypertensive adults enrolled in a practice based research network of 24 primary care practices throughout the state of North Carolina. We analyzed results using descriptive statistics and examined bivariate associations using chi-square and independent associations using logistic regression. Results We received 530 questionnaires (76% response rate). Of 333 respondents (63%) who reported checking their BP in locations other than their doctor's office or home, 66% reported using a monitor stationed in a pharmacy. Younger patients more commonly reported using pharmacy monitors (48% among those < 45 years vs 35% of those over 65, p = 0.04). Blacks reported using them more commonly than whites (48% vs 39%, p = 0.03); and high school graduates more often than those with at least some college (50% vs 37%, p = 0.02). In multivariate analysis, younger age (aOR 1.49; 95% CI 1.00-2.21 for those age 45 to 65 years vs those > 65 years old) and high school education (aOR 1.74; 95% CI 1.13-2.58) were associated with use of pharmacy-stationed monitors, but Black race was not. Patients with diabetes, heart disease, or stroke were not more likely to use pharmacy-stationed monitors. Conclusion Hypertensive patients' use of BP monitors located in pharmacies is common. Younger patients, Blacks, and those with high school education were slightly more likely to report using them. Because use of these monitors is so common, efforts to ensure their accuracy are important.